Optimalisasi Aset Untuk Peningkatan Penerimaan Daerah Melalui Pemanfaatan Ruang Tanah - Ahabun, Hafith (Universitas Islam Kadiri, 2025)
In Law No. 1 of 2022 concerning central and regional financial relations, it is stated that there are 16 taxes for the regions, 7 for the provincial government and 9 for the local government. One of the taxes for the local government is the land and building tax for rural and urban areas (PBB-P2). In the future, the use of underground space and upperground in big cities in Indonesia will increase along with the increasingly limited land space while the need for land space will increase. Permit to grant the right to use the lower and upper room is one solution that can be provided by the government. Multiple benefits will be obtained due to the use of underground space and upperground space, namely an increase in economic activity and an increase in state revenue from the use of underground space and upperground space. The problem is how do we calculate the sale value of the tax object for the use of the basement and the upperground as a tax base. The assessment using the commonly used approach will suit to be applied considering the characteristics of the basement and upperground are different from the land in general. For that we need a special approach or technique in determining the estimated value of an object in the form of a basement and upperground space